Nitrosative stress but not glycemic parameters correlate with improved neuropathy in nonseverely obese diabetic patients after Roux-Y gastric bypass - Müller, Beat P.; Billeter, Adrian; Fleming, Thomas; Fischer, Lars; Büchler, Markus W.; Nawroth, Peter Paul (Surgery for obesity and related diseases, 2015)
Background - Diabetic neuropathy is common in type 2 diabetic patients (T2DM) but tight glycemic control does not improve the symptoms. In contrast, Roux-Y gastric bypass (RYGB) has a positive effect on active neuropathic symptoms, independent from glycemic control. The purpose of the present study was to identify potential mechanisms of improved diabetic neuropathic symptoms after RYGB. - Methods - A prospective cohort of 20 patients with insulin-dependent T2DM and BMI<35 kg/m2 were treated with RYGB. Nineteen patients had complete follow-up. Fasting glucose, HbA1c (glycated hemoglobin), markers for nitrosative, carbonyl, and oxidative stress (nitrotyrosine, carboxylated-lysine (CML), methylglyoxal, oxidized low-density-lipoprotein (oxLDL)) as well as Neuropeptid Y and Neurokinin A were investigated over 12 months. Neuropathy was assessed using the Neuropathy Deficit Score (NDS). - Results - The preoperative NDS improved within twelve months (5.1±0.6 to 2.6±0.4, P = .010). Fasting glucose and HbA1c also improved compared to preoperative values (201.1±16.6 mg/dL to 128±8.7 mg/dL, P = .004 and 8.5±0.3% (53±3.3 mmol/mol) to 7±0.3% (67±3.3 mmol/mol), P = .001, respectively). Nitrotyrosine, CML, and methylglyoxal all 3 decreased postoperatively (1067.3±266.9 nM to 355.8±36.4 nM, P = .003; 257.1±10.2 ng/ml to 215.3±18.3 ng/ml, P = .039; 402.3±3.9 nM to 163.4±10.3 nM, P = .002). OxLDL remained unchanged. Fasting glucose and HbA1c did not correlate with improved neuropathy. The decrease in nitrotyrosine correlated with improvement in the NDS after 6 and twelve months (r = .9, P<.001 and r = .68, P = .03). The decrease in methylglyoxal after 6 months correlated with decrease in NDS after twelve months (r = 0.897, P = .003). - Conclusion - RYGB seems to improve oxidative, nitrosative and carbonyl stress, known to have a causal role in diabetic neuropathy.